Women's Knowledge About Cervical Cancer, Pap Smear and Human Papillomavirus and Its Relation to Screening in Argentina - Paolino, Melisa Delia (2011)
The purpose of this study was to evaluate women?s knowledge about cervical cancer, Pap smears, and human papilloma virus in relation to their cervical cancer screening behavior. This hospitalbased study was conducted with a sample of 200 women: 100 women screened in the last three years and 100 non-screened women who attended a hospital located in the metropolitan area of Buenos Aires, between September 2008 and February 2009. Women at the hospital were surveyed using a structured questionnaire. Multiple logistic regression models were used to evaluate the relation of women?s knowledge about Pap smears to screening behavior, controlling for socio-demographic characteristics. Of the women who had been screened, 49% compared to 73% of those not screened had inadequate knowledge about Pap smears (P D 0.001), and 47% of screened and 30% of non-screened women reported that they had ever heard about human papilloma virus (P D 0.013). In multivariate analysis, having adequate knowledge about Pap smears (odds ratio: 2.6 or 95%, confidence interval: 1.4?4.8) having health insurance (odds ratio: 2.6 or 95%, confidence interval: 1.1?6.4) and being married (odds ratio: 1.8 or 95%, confidence interval: 1.1?3.4) were the factors related to being screened in the previous three years. Knowledge was related to screening. Comprehensive educational approaches may enhance screening for cervical cancer prevention.